DEVELOPMENT OF A SCIENTIFIC WORLDVIEW IN THE TEACHING OF THE TOPIC "THE SUN AND ITS PHYSICAL NATURE" - Akimova, J.; Otarbaev, A. (SCIENCE and SOCIETY, 2024)
This article explores the importance of cultivating a scientific worldview in students through the teaching of the topic "The Sun and its Physical Nature". It discusses the significance of integrating inquiry-based learning, critical thinking, and hands-on experimentation to deepen students’ understanding of solar phenomena. By analyzing existing literature, methods for effective teaching, and the results of implementing these methods, this article highlights the essential role of science education in shaping informed citizens and future scientists.